Rediseño de la red distribución eléctrica y alumbrado público para las calles regeneradas de Saraguro. - Armijos Ramón, Alvaro Jasmanny (2011)
The present thesis project understands "to Redraw the net of electric distribution and illumination public for the regenerated streets of Saraguro". Having as specific objectives: To systematize relative information to the investigation topic, to make a rising of the current electric system in the area to intervene, to implement a study luminotécnico in the execution area and to design a system of distribution electric underground. It is necessary to emphasize the importance of the project, since their study and later execution improved the ornament of the city. Guaranteeing you an appropriate handling of information with dependences as Planeamiento Urbano Municipal and the EERSSA, the same one that I facilitate the projection of the demand (I use of floor and statistical data) for the dimensionamiento of the transformation centers. The regenerated area understands the streets: El Oro, Luis Felipe Ordoñez, Sucre, 10 de Marzo, Loja, José María Vivar, Juan Antonio Montesinos, Honorato Lazo, Pasaje Saraguro y Av. Calasanz;that he/she has an approximate area of 4.7 hectares. He/she was carried out the electric and light study in the study area, being solved to apply a mixed electric system (half tension air, low tension and underground illumination public); in the public illumination you improves the luminance applying normalized factors of illumination. The net of half and low voltage has been projected for a 30 year-old period that is framed in the regulation that regulates theEmpresa Eléctrica Regional del Sur S. A. The budget referencial ascends to the quantity of $ 207.911,18dollars.